EVALUATION OF PRODUCTION SCHEDULING WITH DMAIC METHOD. FCFS. TQC, 5S AT PT GRAFIKA - Henra nanang sukma (Kreator, 2022)
A graphic company can operate well if there is no waste in terms of material, time or process, it is necessary to have PPC in the scheduling department, which can calculate processing time, use process time and monitor production orders. The problem that occurs is scheduling that is not in accordance with the scheduling plan that has been made by the scheduling department, it is necessary to review the scheduling problem and the causes of the discrepancy with the planned scheduling plan. Analysis of the problem using the DMAIC method to identify problems, the FCFS method to calculate the production time delay, there is a delay of 348 minutes or 58 minutes for each job. The TQC method with the 5S method looks at the quality of the production operator. The causal diagram method and the 5W-1H method look for problems that must be resolved immediately, then the causes of delays are found and are not in accordance with the MRT and downtime scheduling plans due to the following factors: A. Production workflow is not clear, b. Incompetent workforce, c. The condition of the engine is problematic, d. Incompatibility of the print production process scheduling plan. Company leaders need to conduct training and understanding of print quality standards in terms of efficiency and time effectiveness. Production costs and workflowÂ Keywords:Â  DMAIC, FCFS, TQC , 5W-1H, scheduling